2019
DOI: 10.14710/ik.ijms.24.2.81-90
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Meiofauna and Physical-Chemical Parameters as Water Quality Indicator

Abstract: The zone of Losari Coast is an icon of Makassar city, however increase activity of surrounding communities causes a decrease in the water quality. Meiofauna is an effective benthic organism used as an indicator of water quality. This study assessed the meiofauna abundance and physical-chemical parameters as water quality indicator in the Losari Coast, Makassar. The sampling method in this study was purposive sampling. The resuts showed that total meiofauna abundance identified was 66791 indv.m-2, composed of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…Dissolved Oxygen concentration around Tunda Island waters in line with the study by Simanjuntak (2007) in Klabat waters on Bangka Island, where DO levels on a surface level (0 m) were 5 m and also the near-bottom waters each range from 3.54 to 4.08 mg/l (3.79 ± 0.10 mg/l); 3.22 to 3.58 mg/l (3.47 ± 0.15 mg/l) and 2.97 to 3.30 mg/l (3.06 ± 0.14 MUJIYANTO MUJIYANTO ET AL S63 mg/l). Yusal et al (2019) found that the range of dissolved oxygen from the north to the south side of Makassar City, South Sulawesi was 3.2 to 5.0 mg/l. This value is considered achievable for meiofauna survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissolved Oxygen concentration around Tunda Island waters in line with the study by Simanjuntak (2007) in Klabat waters on Bangka Island, where DO levels on a surface level (0 m) were 5 m and also the near-bottom waters each range from 3.54 to 4.08 mg/l (3.79 ± 0.10 mg/l); 3.22 to 3.58 mg/l (3.47 ± 0.15 mg/l) and 2.97 to 3.30 mg/l (3.06 ± 0.14 MUJIYANTO MUJIYANTO ET AL S63 mg/l). Yusal et al (2019) found that the range of dissolved oxygen from the north to the south side of Makassar City, South Sulawesi was 3.2 to 5.0 mg/l. This value is considered achievable for meiofauna survival.…”
Section: Discussionmentioning
confidence: 99%
“…The study area Research sampling was done at forty-five stations around Tunda Island, Serang Regency, Banten Province (Figure 1). The study was done using the purposive sampling method, and it was the process of determining the sample based on the selected station as the research subject (Yusal et al, 2019). Data collection was conducted from July to November 2020 in Tunda Island Serang Regency Banten…”
Section: Methodsmentioning
confidence: 99%
“…Topografi Kota Makassar berada pada kemiringan lahan 0-2°(datar) dan kemiringan lahan 3-15° (bergelombang). Wilayah Kota Makassar memiliki luas sekitar 175,77 km persegi dengan kondisi iklim sedang hingga tropis pada kisaran suhu udara rata-rata antara 26-29°C (Yusal & Hasyim, 2017;Yusal et al, 2019aYusal et al, , 2019bYusal et al, , 2019cYusal, 2020b;Yusal, 2021;Yusal and Hasyim, 2022). Sebagian besar Kota Makassar berdekatan dengan wilayah pantai yang membentang sepanjang kawasan barat dan utara yang dikenal sebagai "Waterfront City".…”
Section: Pendahuluanunclassified
“…Peningkatan aktivitas pembangunan Kota Makassar sebagai kota metropolitan telah mereduksi ruang terbuka hijau akibat adanya konversi lahan menjadi perumahan, kawasan industri, jaringan jalan, maupun fasilitas kota lainnya. Hal tersebut telah mengundang datangnya berbagai jenis bencana ekologis yang membawa dampak yang sangat merugikan (Yusal et al, 2019a(Yusal et al, , 2019b(Yusal et al, , 2019c(Yusal et al, , 2019dYusal, 2020b;Yusal, 2021;Yusal & Hasyim, 2022).…”
Section: Pendahuluanunclassified
“…is a series of activities that are the main cause of the entry of pollutants into waters. This condition will certainly affect the quality of the surrounding waters and threaten the existence of organisms that live on the surface and at the bottom of the waters (Yusal, 2017;Yusal et al, 2019cYusal et al, , 2019dYusal et al, 2019aYusal et al, , 2019bYusal, 2020bYusal, , 2020aHandayani et al, 2021;Adrianto et al, 2021;Darmayani et al, 2021a;Darmayani et al, 2021b) These activities have caused the condition of the region to be on the verge of worrying depletion of resources and ecosystems. Several environmental parameters such as physical and chemical are slowly changing towards the negative category.…”
Section: Introductionmentioning
confidence: 99%